Stone cold : a Jesse Stone novel - Parker, Robert B., 1932-2010. (New York : G.P. Putnam's Sons, 2003)
Investigating a thrill-seeking pair of serial killers who are targeting the residents of an affluent suburban town, police chief Jesse Stone finds his job complicated by local politicians, the media, his drinking problem, and his ex-wife.
Keywords: Stone, Jesse (Fictitious character) -- Fiction; Police -- Massachusetts -- Fiction; Police chiefs -- Fiction; Massachusetts -- Fiction; Mystery fiction